2018
DOI: 10.32864/polymmattech-2018-4-2-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Production technology of gears from thermoplastic polymer materials (review)

Abstract: proizvodstva zubchatykh koles iz termoplastichnykh polimernykh materialov (obzor) [Production technology of gears from thermoplastic polymer materials (review)]. Polimernye materialy i tekhnologii [Polymer Materials and Technologies], 2018, vol. 4, no. 2, pp. 6-31. Литература Для приобретения полного текста статьи, обращайтесь в редакцию журнала Full text of articles can be purchased from the editorial office

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…It is known that to grind the teeth in gears by copying, they are placed almost vertically in the grinding area and ground [2,6,15]. It has been established that, analogously to shaped turning surfaces, the actual cutting depth determined in the vertical direction in a tooth grind with copying varies along the involute profile of the tooth [9,13].…”
Section: Development Of a Methods For Grinding Involute Profiles Of T...mentioning
confidence: 99%
“…It is known that to grind the teeth in gears by copying, they are placed almost vertically in the grinding area and ground [2,6,15]. It has been established that, analogously to shaped turning surfaces, the actual cutting depth determined in the vertical direction in a tooth grind with copying varies along the involute profile of the tooth [9,13].…”
Section: Development Of a Methods For Grinding Involute Profiles Of T...mentioning
confidence: 99%
“…In reference [ 25 ], it was noted that injection moulding technology can be used to mould gears from polyacetal. Reference [ 26 ] demonstrated that Hostaform polyacetal is suitable for manufacturing screw gears, conveyor rollers, holders, sliding bearings, and parts of conveyor chains.…”
Section: Introductionmentioning
confidence: 99%
“…Анализ производства современных малогабаритных зубчатых (кинематических) передач позволил выявить следующие особенности. В основном проектируют и изготавливают одноступенчатые и малогабаритные передачи из конструкционных полимерных композиционных материалов и преимущественно мелкосерийными партиями [2]. Достаточно широко стали использовать для изготовления таких зубчатых передач 3D-принтеры в основном в индивидуальном производстве [3][4][5].…”
unclassified